TOWARDS A UNIVERSAL AND COMPREHENSIVE HEALTH CARE COVERAGE FOR MALAYSIANS - Rohaizat BY; Mahani AH; Yao SK; Mohd Ismail M (Malaysian Journal of Public Health Medicine, 2004)
Health is closely related with social welfare. It is also associated with the condition of a person’s body and mind. The universal and comprehensive coverage of health care is defined as physical and financial access to necessary health care of good quality for all persons in a society. The extension of the concepts of coverage should include both the depth and breath of coverage. Therefore to provide comprehensive health care coverage for Malaysians would mean providing both health care services as well as health rdated services such as social services. Although the Malaysian health care system is a success story among countries of equivalent socio ... economic status, there are however stilr numerous issues and challenges faced by the nation, thereby creating the need for changes and reform in health care financing. It is hoped that with the establishment of the national health financing mechanism, greater coverage, access and equity to both public and private health sectors could be provided for all Malaysians.